2011
DOI: 10.3354/dao02306
|View full text |Cite
|
Sign up to set email alerts
|

Widespread survey finds no evidence of Haplosporidium nelsoni (MSX) in Gulf of Mexico oysters

Abstract: The advent of molecular detection assays has provided a set of very sensitive tools for the detection of pathogens in marine organisms, but it has also raised problems of how to interpret positive signals that are not accompanied by visual confirmation. PCR-positive results have recently been reported for Haplosporidium nelsoni (MSX), a pathogen of the oyster Crassostrea virginica in 31 of 40 oysters from 6 sites in the Gulf of Mexico and the Caribbean Sea. Histological confirmation of the PCR results was not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…infecting gastropods only form a monophyletic group (H. pickfordi, H. tuxtlensis, H. montforti, and H. lusitanicum) as opposed to the rest of the Haplosporidia occurring in Bivalvia. Ulrich et al (2007) reported H. nelsoni in the Gulf of Mexico, but subsequent studies have cast doubt on the methods used for detection of parasites (Burreson, 2008), and no evidence from further surveys detected H. nelsoni in this area (Ford et al, 2011). Haplosporidium tuxtlensis is, therefore, the first confirmed record of a haplosporidian parasite species in the Gulf.…”
Section: Discussionmentioning
confidence: 93%
“…infecting gastropods only form a monophyletic group (H. pickfordi, H. tuxtlensis, H. montforti, and H. lusitanicum) as opposed to the rest of the Haplosporidia occurring in Bivalvia. Ulrich et al (2007) reported H. nelsoni in the Gulf of Mexico, but subsequent studies have cast doubt on the methods used for detection of parasites (Burreson, 2008), and no evidence from further surveys detected H. nelsoni in this area (Ford et al, 2011). Haplosporidium tuxtlensis is, therefore, the first confirmed record of a haplosporidian parasite species in the Gulf.…”
Section: Discussionmentioning
confidence: 93%
“…Distilled water was used to bring the final reaction volume to 20 μl. The thermal cycling protocol consisted of a 95°C hold for 10 min followed by 45 cycles of (Ford et al 2011, OIE 2021.…”
Section: Multiplex Qpcr Reactionmentioning
confidence: 99%
“…Previously, H. nelsoni had been reported only from the Atlantic coast of North America, never in the Gulf of Mexico, so this report created uncertainty about potential movements of shellfish, even shellfish gametes, from the Atlantic to the Gulf coasts of North America. Subsequently, an extensive survey was unable to confirm the presence of H. nelsoni in the Gulf of Mexico [74]. This example points to the need for diligent surveillance.…”
Section: The Paradox Of Uncertainty In Shellfish Disease Managementmentioning
confidence: 99%